2017
DOI: 10.1111/pedi.12574
|View full text |Cite
|
Sign up to set email alerts
|

Prefronto‐temporal white matter microstructural alterations 20 years after the diagnosis of type 1 diabetes mellitus

Abstract: Widespread WM microstructural abnormalities in the fronto-temporo-parietal brain regions, which are associated with emotional and cognitive dysfunction, may be a contributing factor to the neural mechanisms underlying T1DM-related CNS complications, thus affecting the quality of life in young adults with T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
(140 reference statements)
0
10
0
Order By: Relevance
“…A total of eight of the included studies consistently revealed the reduction of FA in T1DM [ 2 , 4 , 21 , 22 , 23 , 24 , 25 , 26 ], while four studies revealed higher MD, RD and AD in the white matter of T1DM patients compared to healthy controls ( Table 2 ) ( Figure 4 ) [ 4 , 20 , 21 , 26 ]. Most of the studies analysed DTI images using only voxel-wise brain analysis while other studies used both region of interest (ROI) and voxel-wise analysis [ 22 , 26 ], except for one study which used DTI tractography [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of eight of the included studies consistently revealed the reduction of FA in T1DM [ 2 , 4 , 21 , 22 , 23 , 24 , 25 , 26 ], while four studies revealed higher MD, RD and AD in the white matter of T1DM patients compared to healthy controls ( Table 2 ) ( Figure 4 ) [ 4 , 20 , 21 , 26 ]. Most of the studies analysed DTI images using only voxel-wise brain analysis while other studies used both region of interest (ROI) and voxel-wise analysis [ 22 , 26 ], except for one study which used DTI tractography [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings of included studies suggest that longer disease duration and increased HbA1c values correlated with the severity of microstructural abnormalities in optic radiation [ 2 , 23 ], posterior corona radiata [ 2 ], right internal capsule, anterior forceps, inferior frontal occipital fasciculi, splenium of the corpus callosum [ 2 ], uncinate fasciculi, subgenual white matter, superior, middle and inferior temporal gyri, superior longitudinal fasciculi, and occipital white matter [ 20 , 21 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be noted that alterations in brain white matter have been observed among individuals with Type I and Type II diabetes (Moghaddam, Sherbaf, & Aarabi, ; Yoon et al, ). The present analyses included two individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%